Post-COVID-19 menstrual abnormalities and infertility: Repercussions of the pandemic - Sparsh Madaan; Dhruv Talwar; Arpita Jaiswal; Sunil Kumar; Neema Acharya; Sourya Acharya; Deepika Dewani (Wolters Kluwer Medknow Publications, 2022)
While battling the life-threatening complications of COVID-19, its effect on the menstrual cycle and infertility has been somewhat ignored. This brief review aims on highlighting the importance of menstrual abnormalities being experienced during the post-COVID period and to make the clinicians aware about what to expect in regard of menstrual abnormalities by learning from various studies that have been conducted worldwide. This review article was written with systematic literature review with the help of data search machine such as PubMed, Scopus, Web of Sciences, and Google Scholar.A search strategy leads to the extraction of 160 related articles that after the removal of inappropriate and duplicate articles, 33 articles were selected for the review. To find other potentially relevant articles, the references of the extracted articles were thoroughly examined. The search was carried out using keywords including "COVID-19," "Menstrual abnormalities," and "Infertility." Using OR and AND, the keywords mentioned above were combined and then utilized in the search box of the databases. Articles published from January 2020 to September 2021 were included in this study. It includes worldwide data ranging from studies done in China, India, Ireland, Turkey, Jordan, and Germany. During the post-COVID period, there is a significant alteration in the sex hormones of females infected by COVID-19 which may manifest as menstrual cycle abnormalities such as decreased cycle length or prolonged menstrual cycle bleeding. It may also manifest as infertility due to ovarian failure due to suppression of ovarian function COVID-19 a novel coronavirus which is presently a pandemic has affected the world in manner reminding the world of 1918 Spanish flu. However, while battling the deadly pandemic, the clinicians should also be aware of the repercussions of the effect this infection has on multiple organs such as ovarian suppression leading to infertility, oligomenorrhea, or menorrhagia.